Intersectional dehumanization in faces: Facial attractiveness and perceived intelligence differentially predict dehumanization across intersecting race and gender identities - Neelamberi Devi Klein; Kurt Hugenberg (PLoS ONE, 2026)
Past work has found that more attractive and more intelligent appearing faces are ascribed more humanlike sophistication at zero acquaintance, but past work has only employed White faces. Of interest in the present work is whether similar effects occur across target race. Across two studies we investigate if the relationships between attractiveness and perceived intelligence vary across Black and White, male and female faces. Across both studies, we find that more attractive faces are evaluated as more humanlike across target race and gender, but notably that target race moderates the predictiveness of perceived intelligence. Perceived intelligence only relates to humanness for White targets, but not Black. These findings provide support for the theory that face trait relationships are often dependent on target identities, such as race and are consistent with extended research indicating that Black Americans’ minds may be devalued.